Frequency of Chikungunya virus infection in samples tested concomitantly for dengue and malaria: experience from clinical laboratory, Karachi Pakistan - Shahid, Uzma; Farooqi, Joveria; Mailk, Faisal Riaz; Khan, Erum (Infectious Diseases Journal of Pakistan, 2022)
Background: Chikungunya virus (CHIKV) has recently emerged as cause of acute febrile illness. Exact burden of this viral infection in Pakistan, is not known. A cross-sectional study was performed to assess the frequency of CHIKV infection tested in a clinical laboratory as compared to that of dengue and malaria. Methods: A descriptive cross-sectional study was conducted over a period of 6 months, at the section of microbiology, Aga Khan University Hospital Clinical Laboratories (AKU), in Karachi. Samples for detection of dengue Non-structural protein 1 antigen (NS1Ag) and/or Immunoglobulin M (IgM), Chikungunya IgM and Malaria Immuno-Chromatographic Testing (ICT) from patients of all ages and both genders were selected and enrolled. Result: A total of 13,271 patient samples with acute febrile illness were received during the study period. Of which (N= 10160) were tested for malaria, (N=1484) were tested for dengue and (N= 595) for Chikungunya infection. Chikungunya IgM was detected in 8.2% (49 cases) samples. Most cases were diagnosed with malaria (256 cases, 2.5% of those tested) and dengue (251 cases, 16.9% of those tested). Conclusion: We found CHIKV to be a common cause of febrile illness, its proportion of positive results second only to dengue. However, the burden of dengue and malaria experienced at AKU was much higher than CHIKV. Chikungunya is active in the region and should be considered as an important differential for febrile illnesses. Key words: Chikungunya, Dengue, Malaria, Frequency, Pakistan.